Tilghman B. Crossing boundaries / trans. from Engl. I. N. Nekhaeva - I. N. Nekhaeva (Омский научный вестник: Серия "Общество. История. Современность")
There is much talk in the «art world» about boundaries and the blurring of boundaries between art and non-art, art and craft, and various forms within art. What is meant by a boundary is not always clear and this paper tries to make some sense of what may be at stake when deciding on which side of a line something falls. It is suggested that the important thing is how we deal with and react to particular examples rather than worrying about whether it is a this or a that